2015 37th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2015
DOI: 10.1109/embc.2015.7320282
|View full text |Cite
|
Sign up to set email alerts
|

Unsupervised HEp-2 mitosis recognition in indirect immunofluorescence imaging

Abstract: Automated HEp-2 mitotic cell recognition in IIF images is an important and yet scarcely explored step in the computer-aided diagnosis of autoimmune disorders. Such step is necessary to assess the goodness of the HEp-2 samples and helps the early diagnosis of the most difficult or ambiguous cases. In this work, we propose a completely unsupervised approach for HEp-2 mitotic cell recognition that overcomes the problem of mitotic/non-mitotic class imbalance due to the limited number of mitotic cells. Our techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…However, their method showed a poor result for classifying the positive mitotic class, achieving a true positive rate of 51.7%. Alternatively, Tonti et al [ 31 ] suggested a completely unsupervised approach to differentiate the minority mitotic cell images from the remaining interphase cell images based on predefined rules on the morphological and texture GLCM [ 32 ] descriptors. The best classification accuracy from their method was achieved at 75.6%.…”
Section: Related Workmentioning
confidence: 99%
“…However, their method showed a poor result for classifying the positive mitotic class, achieving a true positive rate of 51.7%. Alternatively, Tonti et al [ 31 ] suggested a completely unsupervised approach to differentiate the minority mitotic cell images from the remaining interphase cell images based on predefined rules on the morphological and texture GLCM [ 32 ] descriptors. The best classification accuracy from their method was achieved at 75.6%.…”
Section: Related Workmentioning
confidence: 99%
“…The correct identification of the HEp-2 pattern helps identifying the type of antibody, hence it indirectly allows a differential diagnosis of the autoimmune disease. In the last few years, many researchers have exploited the analysis of HEp-2 textures to either perform the automated classification of HEp-2 patterns [22], [23], the automated segmentation of HEp-2 cells [24], [25] or the recognition of mitotic processes within the HEp-2 samples [26], [27], which are all important tasks in the ANA testing procedure.…”
Section: Texture Analysis In Biological Imagingmentioning
confidence: 99%
“…Hence, the PC module is completely independent from the IC module, in that it does not need to receive intensity as an input parameter. (ii) mitotic cell detection as reported in [36] is applied in order to identify and remove the mitotic cells (i.e. cells undergoing cellular division).…”
Section: Pattern Classifier (Pc)mentioning
confidence: 99%